THE EFFECT OF OUTING CLASS-BASED CONTEXTUAL LEARNING MODELS ON THE ENGLISH VOCABULARY OF MTs LABORATORY STUDENTS UINSU MEDAN - Yamsin, Mulia Ourora (BRIGHT VISION Journal of Language and Education, 2024)
This research aims to determine the effect of an outing class-based contextual learning model on the English vocabulary of class VIII MTs Laboratory UINSU Medan. The research population consisted of all class VIII students at the Madrasah Tsanawiyah Laboratory of UINSU Medan. This means that the population is all members of a certain place. The population of this study was 120 class VIII students. The sample is representative of the research population. The sample was determined using random sampling so that two classes with a total of 60 students from class VIII were selected as research samples for the experimental class and control class. Data analysis techniques by comparing the mean descriptive statistics of quantitative data to determine the differences before and after the test in the average pre-test and post-test scores.The research results show that there is an influence of the outing class- based contextual learning model on the English vocabulary of class VIII MTs Laboratory UINSU Medan. It is important to suggest that teachers as English language teachers in general, especially in class VIII MTs Laboratory UINSU Medan, place more emphasis on teaching using contextual learning models based on outing classes. Further research needs to be conducted on the differences between teaching English using contextual learning models, especially for researchers who intend to conduct research using the same objects in order to obtain more perfect results.